Revelation of fibroblast protein commonalities and differences and their possible roles in wound healing and tumourigenesis using co-culture models of cells - Jarkovska, Karla; Dvorankova, Barbora; Halada, Petr; Kodet, Ondrej; Szabo, Pavol; Gadher, Suresh Jivan; Motlik, Jan; Kovarova, Hana; Smetana, Karel (Biology of the cell, 2014)
BACKGROUND INFORMATION: The in vitro co-culture models of communication between normal fibroblasts and epithelial cells, such as keratinocytes or squamous cell carcinoma cells of FaDu line representing wound healing or cancer development, were established by non-direct contact between the cells and utilised in this study to examine epithelia-induced changes in overall fibroblast proteome patterns. RESULTS: We were able to select the proteins co-regulated in both models in order to evaluate possible molecular commonalities between wound healing and tumour development. Amongst the most pronounced were the proteins implemented in contractile activity and formation of actin cytoskeleton such as caldesmon, calponin-2, myosin regulatory light-chain 12A and cofilin-1, which were expressed independently of the presence of α-smooth muscle actin. Additionally, proteins altered differently highlighted functional and cellular phenotypes during transition of fibroblasts towards myofibroblasts or cancer-associated fibroblasts. Results showed coordinated regulation of cytoskeleton proteins selective for wound healing which were lost in tumourigenesis model. Vimentin bridged this group of proteins with other regulated proteins in human fibroblasts involved in protein or RNA processing and metabolic regulation. CONCLUSIONS: The findings provide strong support for crucial role of stromal microenvironment in wound healing and tumourigenesis. In particular, epithelia-induced protein changes in fibroblasts offer new potential targets which may lead to novel tailored cancer therapeutic strategies.
Keywords: hojení ran; mezibuněčná komunikace; Contractile proteins; cytoskelet; Humans; kokultivační techniky; regulace genové exprese; Cytoskeleton; Keratinocytes; Carcinogenesis; Tumourigenesis; keratinocyty; lidé; Cell Communication; Wound Healing; myofibroblasty; Coculture Techniques; Cytoskeletal Proteins; cytoskeletální proteiny; Gene Expression Regulation; Cancer-associated fibroblasts; karcinogeneze; Myofibroblasts; Tissue injury; nádorové buněčné linie; spinocelulární karcinom; fibroblasty; Carcinoma, Squamous Cell; Cell Line, Tumor; transdiferenciace buněk; Cell Transdifferentiation; Fibroblasts